Social Capital At The Darussalam Islamic Boarding School In Martapura - Siti Zulfah; Mutiani Mutiani; Muhammad Rezky Noor Handy; Jumriani Jumriani; Sigit Triyono (Program Studi Pendidikan IPS, 2025)
Social capital is a crucial concept in understanding social interactions in society, encompassing elements such as trust, social networks, and norms that support cooperation. This article discusses the role of social capital in the context of the Darussalam Islamic Boarding School, where trust between individuals, both between ustadz and santriwati, plays an important role in creating a productive educational environment. By prioritizing good communication and positive interactions, trust is built through shared experiences and involvement in religious activities. The Banjar community is an example of how trust can be formed through kinship relationships and open communication. The effective application of social capital in the Islamic Boarding School not only produces quality santriwati, but also creates a safe and harmonious atmosphere that encourages cooperation and mutual respect among all members of the community. Through this approach, social capital is expected to strengthen social ties and increase individual productivity in society.